2019
DOI: 10.1590/1806-9282.65.1.3
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, treatment, and control of dyslipidemia in diabetic participants of two brazilian cohorts: a place far from heaven

Abstract: SUMMARY OBJECTIVE Diabetes is one of the leading causes of cardiovascular mortality. Over the last years, mortality has decreased significantly, more in individuals with diabetes than in healthy ones. That is mostly due to the control of other cardiovascular risk factors. The objective of our study was to analyze the dyslipidemia control in two diabetes cohorts. METHODS Patients from two distinct cohorts were studied, 173 patients from the BHS (Brasília Heart Study) and 222 patients from the BDS (Brazilian… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…Perhaps high-income population groups have greater access to healthier foods such as fruits, vegetables, and low-fat alternatives. Indeed, a Brazilian study analyzed the treatment for dyslipidemia among patients with diabetes and observed that people with higher socioeconomic levels have better follow-up by private or insurance doctors, possibly explaining better health outcomes 16 .…”
Section: Resultsmentioning
confidence: 99%
“…Perhaps high-income population groups have greater access to healthier foods such as fruits, vegetables, and low-fat alternatives. Indeed, a Brazilian study analyzed the treatment for dyslipidemia among patients with diabetes and observed that people with higher socioeconomic levels have better follow-up by private or insurance doctors, possibly explaining better health outcomes 16 .…”
Section: Resultsmentioning
confidence: 99%
“…These factors make it difficult to reach desirable glycemic and lipid levels and increase cardiovascular risk. 2,22 In view of the above, there is a need to clarify to these patients the importance of adopting lifestyle changes, such as physical exercise and smoking cessation, as well as the recognition and ways to deal with risk factors to improve disease management. Although the variable alcohol consumption did not show sta-tistical significance, it is important to inform the patient about the harm that excessive alcohol consumption can cause, such as increased risk of hypertriglyceridemia.…”
Section: Discussionmentioning
confidence: 99%
“…When poorly controlled, DM2 also affects the lipid metabolism of the patient with the disease and can lead to dyslipidemia. [1][2][3] Added to this, the person with diabetes also tends to have an accumulation of adiposity that, in turn, generates a pro--inflammatory state, insulin resistance, and increases the risk of developing atherosclerosis and other major cardiovascular complications. Such an imbalance can lead to dysregulation of the immune system, facilitating infection of the patient by infectious diseases, such as COVID-19.…”
Section: Introductionmentioning
confidence: 99%
“…Cardiovascular and cerebrovascular diseases caused by atherosclerosis as a result of dyslipidemia are the leading causes of death worldwide. Dyslipidemia and diabetes mellitus are one of the most common causes of atherosclerosis worldwide [1]. The TyG index, which is calculated to predict these diseases that cause serious mortality and morbidity, is both practical and advantageous in that it can be scanned in the entire population [2].…”
Section: Introductionmentioning
confidence: 99%